Mondialization, im perialist globalization and latin am erican cities (2009)
By changing the state interventionist pattern of capital accumulation to a neoliberal’s one, the ideology of globalization start prevailing and was adopted uncritically by researchers from all streams, including numerous from Latin American. Despite the intensification of the exploitation of workers, the prowling of nations and preventive war, it is thought to be unavoidable, positive and that it generates societies and territories without contradictions. This paper shows that capitalist mondialization began in the sixteenth century, and developed differentially and unequal in societies, territories and cities. The current imperialist stage dominated by three blocs led by United States of America -USA-has used different patterns of accumulation, does not guarantee a sustained and sustainable accumulation of capital, it does not improves quality of life of people, nor eliminates the inequality between nations, regions and cities in Latin America. In the same way, the global city concept is inapplicable in our regions, whose cities are subordinated and undergo processes of deindustrialization and outsourcing predominantly informal.